Blue Hydrogen and Ammonia - Bahbishi, Saad; Alwossabee, Abdulatif; Almousa, Zahrah (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
As the world seeks to transition to a low-carbon energy sources to meet the decarbonization goals for 2050, there is an essential need for technologies that can significantly reduce CO2 emissions without compromising the global energy and industrial production demands. Among the low-carbon energy alternatives being explored, blue hydrogen and ammonia are considered as practical options. These elements offer promising potential as energy carriers and fuels to significantly reduce carbon emissions across different industries. However, like any emerging technology, blue hydrogen and ammonia come with their unique challenges and obstacles that must be addressed for wider implementation. Before going further into the details of research, it is important to understand the connection between hydrogen and ammonia, and the reason why ammonia is critical in supporting hydrogen as an energy carrier. This technical paper will explore the different types of hydrogen and ammonia, which are categorized based on their production source and methods. These variations also have significant impact on production costs. Hydrogen and ammonia are recognized as an element that can generate substantial energy. However, a key question remains: Can they compete with conventional energy sources, such as hydrocarbons? And if they hold such promise, why haven’t they fully replaced traditional energy sources yet?